PERANCANGAN CERGAM PENGETAHUAN TENTANG TANAMAN BERACUN NUSANTARA - INDRIATI SUCI.P S1 (Saraswati)
ABSTRACTIndonesia is one country in the world that has two seasons namely the rainy and dry due tothe influence of those two seasons, Indonesia has diverse plant species, including various typesof dangerous plants, according to experts, 10% of all flowering plant species in the world is inIndonesia , meaning that Indonesia has approximately 25,000 flowering plant species, and whencoupled with non flowering plants and fungi, then the amount will be many times.Of the total crop was nothing toxic, nothing to eat, and there are advised not to eat. Thework of this thesis is essentially like the member information about the types of plants or toxic ornegative impact when consumed by humans is one example of the dangers of consuming jengkolcontaining acid Jengkolat / djencolic acid can cause a chalky urine with blood and prolongedpain. In addition to the importance of the knowledge of poisonous plants for the climbers to notcarelessly consume plants that are in the woods or mountains, various shapes and forms andcolors of both types of plants and flowers often invite curiosity that led to the taking of plantsand flowers are actually harmful to touched or consumed.The number of cases of poisoning caused by the lack of public knowledge about poisonousplants because sometimes poisonous plant that is often consumed and growing and close to thedaily life of one example of the amanita mushroom phaloides similar to mushroom, the effort toget the hang of the easiest is to use picture story media, essentially the case that often arisespoisoning contributed to the formulation of the design for cergam Plants Toxic Archipelago, acomprehensive community will be given the knowledge ranging from the definition of poisonousplants, poisonous plants characteristics, range of issues and causes toxic poisoning, poisonousplants, and how poisoning prevention happens through the mouth, nose (inhalation), skin, eyes,stings and bites of venomous animals.The point is to talk about issues cergam poison and its consequences with a different andfun to learn, because cergam an effective medium of learning about science and can providedirect overview of the science that will be delivered a lot contain elements of art, the need fordesign the title of the final paper work is "designing cergam knowledge of poisonous plantsarchipelago".Keywords: Plants Toxic, Toxic, Toxic Plants archipelago.1